SHEAR BEHAVIOUR OF REINFORCED-CONCRETE BEAMS INCORPORATING IRON FILINGS AS SAND REPLACEMENT (Advances in Civil and Architectural Engineering, 2023)
This study examined the influence of partial sand replacement with iron filings on the mechanical and physical characteristics of concrete, as well as conducted experimental tests of the shear behaviour of reinforced-concrete beams. Four replacement rates were used in this study, i.e., 5 %, 10 %, 20 %, and 30 % with a reference mixture containing no iron filings. At ages 7, 14, and 28 days, mechanical property tests (slump, density, ultrasonic pulse velocity, compressive strength, and splitting strength tests) were conducted. In addition, the shear behaviour of five reinforced-concrete beams with the same replacement rates (0 %, 5 %, 10 %, 20 %, and 30 %) were experimentally tested. Tests were conducted to determine the ultimate load failure, final deflection, energy absorption, stiffness, ductility index, compressive stress, and crack formations. According to the results, the correlation between the slump test and iron filings is positive; however, that for absorption is negative. With a higher percentage of iron-filing replacement, the density and ultrasonic pulse velocity increased. For specimens with 30,00 % iron filings, the densities, pulse velocities, and slumps were raised by 6,27 %, 2,44 %, and 58,33 %, respectively, compared to the reference specimens, whereas the absorption rate decreased by 20,00 %. Having 20,00 % iron filings produced the maximum compressive and splitting strengths of 28,00 %, which was 4,60 % higher than the reference mixture, whereas 30,00 % iron filings produced the highest flexural strength, which was 9,50 % higher than the reference mix. The findings of beam testing revealed that increasing the iron-filing content in concrete beams increased the final failure load, final deflection, ductility index, and energy absorption by 6,70 %, 10,29 %, 11,30 %, and 35,00 %, respectively. The initial and secant stiffnesses decreased at rates of 12,60 % and 3,10 %, respectively.